2018
DOI: 10.1016/j.scitotenv.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between landslides and mountain development—Integrating geospatial statistics and a new long-term database

Abstract: Development in mountainous areas is inevitable in countries with high population densities, but the actual relationship between development and landslides remains uncertain. Clarifying the key current or historical factors resulting in landslides is crucial for hazard prevention and mitigation. This study focused on the Shihmen Reservoir catchment in Taiwan. Two combinations of explanatory variables in five different years (1946, 1971, 2001, 2004, and 2012) collected from a geodatabase and digital archives wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Figure 1 also shows the land use feedbacks in the influences of the natural environment. Changes in land use drive changes in hazard distribution [6,[34][35][36][37]39]. More specifically, effective land management helps mitigate soil erosion [37,39].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 also shows the land use feedbacks in the influences of the natural environment. Changes in land use drive changes in hazard distribution [6,[34][35][36][37]39]. More specifically, effective land management helps mitigate soil erosion [37,39].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In particular, in mountainous areas, landslides are frequently caused by increased rainfall [1]. Landslides manifest as mountain attachments (e.g., rocks, debris and earth) sliding downward with gravity [5] that pose a great threat to the lives and property of residents [6][7][8][9][10][11]. Between 1990 and 2005, landslides accounted for 4.8% of the total number of global disasters [7].…”
Section: Introductionmentioning
confidence: 99%
“…Landcover: According to Khan, Shafique [4], Land cover has a strong influence on the distribution of landslides. An evidence that good vegetation cover would work effectively to retain water generation, reduce erosion and then improve the stability of the area [5]. In a recent study, Reichenbach, Rossi [2] have suggested an equal contribution weight to landslide between land cover and precipitation.…”
Section: Figure 3 Flowchart Of the Methodology Adopted For This Studymentioning
confidence: 99%
“…Paola Reichenbach et al (2018) classed 23 landslide impact factors into five groups of causatives which are: geological, hydrological, land cover, morphological and other factors. Nevertheless, the proportion of contribution of the causative factors to landslide occurrence is different depending on spatial, temporal distributions of the event [1,2,3,4,5]. Recent studies which focus on Asian countries such as China, Taiwan, Korea and Japan indicate that duration and magnitude of rainfall are primary causatives of landslides in mountainous areas [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation